Inkjet printing ceramics: From drops to solid - Derby, B. (Journal of the European Ceramic Society, 2011)
Inkjet printing is a powerful microfabrication tool that has been applied to the manufacture of ceramic components. To successfully fabricate ceramic objects a number of conditions must be satisfied concerning fluid properties and drop placement accuracy. It has been proposed that fluids are printable within the bounds 1 < Z < 10 (where Z is the inverse of the Ohnesorge number) and these limits are shown to be consistent with ceramic suspensions delivered by piezoelectric drop-on-demand inkjet printers. The physical processes that occur during drop impact and spreading are reviewed and these are shown to define the minimum feature size attainable for a given printed drop diameter. Finally the defects that can occur during the drying of printed drops are reviewed (coffee staining) and mechanisms and methodologies to reduce this phenomenon are discussed.